Analysis Of Welfare Levels Of Rattan (Calamus Axillaris) Home Industrial Craftsman in Central Waitatiri Production in Suli Village, District Salahutu Central Maluku District - Juni Ardin Telaumbanua; Jeter D Siwalette; Marfin Lawalata (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
This study aims to determine the development of the rattan home industry and determine the level of welfare of the rattan home industry craftsmen in Suli Village, Salahutu District, Central Maluku Regency. The research locations were selected using a census. The data collected in the study are primary data and secondary data. Research results based on The development of the rattan home industry have existed since the 60s as many as 20 more rattan craftsmen now have become home industries or household scale as many as 13 production houses are still managed by the Toraja tribe for generations and not indigenous people. Based on the welfare level of the rattan home industry craftsmen according to BPS 2008, there are 2 rattan craftsmen with a near-poor level of welfare with a percentage (15.4%), 5 rattan craftsmen with a prosperous welfare level III with a percentage (38.5%) and 6 rattan craftsmen with a welfare level of prosperous farmers III Plus with a percentage (46.1%). From the 2008 BPS indicators, the Welfare Level of Rattan Home Industry Craftsmen in Suli Village, Salahutu District, Central Maluku Regency, on average, belongs to the family of prosperous farmer welfare level III Plus. Keywords: Welfare Level, Home Industry, Rattan Crafts